Coordination of parental performance is breeding phase-dependent in the Dovekie (Alle alle), a pelagic Arctic seabird. - Antoine Grissot; Lauraleen Altmeyer; Marion Devogel; Emilia Zalewska; Clara Borrel; Dorota Kidawa; Dariusz Jakubas; Katarzyna Wojczulanis-Jakubas (PLoS ONE, 2024)
Currently, parental care is becoming increasingly perceived as male and female cooperation, instead of being primarily shaped by sexual conflict. Most studies examining cooperating performance consider coordination of parental activities, and doing so focuses on a short time-window including only one stage of breeding (i.e., incubation or chick rearing period). Here, we considered the cooperation of breeding partners, investigating the coordination of parental care in a long-lived seabird species with long and extensive biparental care, the Dovekie (or Little Auk), Alle alle, and looked at the issue throughout the breeding season. Previous studies on this species revealed coordinated chick provisioning, but parental coordination during incubation remains unstudied. Using video recordings collected over the course of two breeding seasons, we tested whether coordination was subject to small-scale changes within each stage and whether there was a relationship between coordination levels across the two stages. We found that the level of parental coordination is overall high and increases during the incubation period but decreases through the chick rearing phases. There were some inter-annual differences in the coordination level both at the incubation and chick rearing stages. We also found some dependency between the coordination during the incubation and chick rearing periods. All these results suggest that coordination is not a fixed behavior but breeding-phase dependent. The present study thus provides insights into how parental care and parents' cooperation is shaped by brood needs and conditions. It also highlights a relationship between coordination levels during chick rearing and incubation periods, suggesting some extent of temporal dependence in coordination of parental performance within the breeding season.